Undervaluation of new technologies for mass tort redress in the light of the new european guidelines and their impact on Spanish Law - MORENO CORDERO, Gisela (Revista Jurídica Portucalense, 2022)
In late closing, Directive (EU) 2020/1828 of the European Parliament and of the Council, of November 25, 2020, on representation actions for the protection of the collective interests of consumers was approved. The main objective set by the Directive has been to ensure that consumers in all Member States have at least one process mechanism capable of effectively protecting their collective interests. However, his proposal is based on a highly ineffective litigation model of legal actions and has not been considered as a result of the experience accumulated in several Member States of proven effectiveness in time and results, such as regulatory redress and ombudsman. The transposition of the directive will sow important rights for state legislators whose ordinances have a less evolved mechanism of collective action than the design proposed by the community legislator, as in the Spanish case. Taking this path would be very compromised knowing that the reparation of the consumer who claims before the Spanish authorities can take a long time to materialize, a fact that alone convinces the "efficiency" proclaimed in the Directive on vacuum heat.